Knowledge, attitude and practice of using personnel protective equipment among Radiographers attending COVID-19 patients / Mohd Hanif Mohd Nor and Mohd Hafizi Mahmud - Mohd Nor, Mohd Hanif; Mahmud, Mohd Hafizi (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Knowledge, attitude, and practices are three important aspects to understanding and analysing the behaviour of healthcare workers thoroughly. This study aims to evaluate the knowledge, attitude, and practice of using personnel protective equipment (PPE) among radiographers attending COVID19 patients. A cross-sectional survey using a validated questionnaire was distributed to radiographers (n=50) at a radiology hospital of a health institution. The questionnaire comprised six knowledge, eight attitudes and 17 practice questions related to PPE. 86% (n = 43) had knowledge while 64% each (n = 32) possessed positive attitude and good practice, respectively. The radiographers demonstrate good knowledge of PPE when attending to COVID-19 patients. Although generally, the attitude and practice of the radiographers were good, donning and doffing of PPE was identified as an area for improvement.